Automatic Face Composition selection using perception based - Mahaisavariya, Jaturong; Sucontphunt, Tanasai (Journal of Applied Statistics and Information Technology, 2018)
This research presents experiment evaluation of algorithms to selecting the appropriate facial cartoon shapes for generating cartoon face by using only one photo without human decision. Each algorithm which has highest precision from selecting testing data compare with shapes selected by specialist who specialize in composing cartoon face. Form the experiment, the most accurate classifier and observation will consider as the most appropriate algorithm for selecting each facial component i.e. eye brow used CentroidVectorLength and Neural Net, eye used CrossVectorLength and Decision Tree, Face shape used CrossVectorLength and Decision Tree, mouth used CentroidVectorAngle and Decision Tree and nose used CentroidVectorLength and Decision Tree. Even system cannot replace into all automatic system but this work can be applied to various applications such as game, social media and entertainment business.